2021
DOI: 10.2147/jmdh.s325269
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Practice of Physical Activity and Lifestyle of Students During COVID-19 Lockdown

Abstract: Purpose: Several factors influence the student's physical activity and lifestyle. The coronavirus disease (COVID-19) lockdown has restricted student's activity and altered their routine lifestyle. This prospective cohort study aimed to determine the significant changes in body mass index (BMI), physical activity, and lifestyle of the students including diet, sleep, and mental health before and during COVID-19 lockdown. Methods: The study participants were 628 students studying bachelor's degree programs, betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 51 publications
9
78
0
3
Order By: Relevance
“…The results of this study show that significant changes have occurred, including decreased physical activity and increased sedentary, sleep and screen time [18]. Similar to our results are data from a study conducted in Saudi Arabia, according to which most students report poor physical activity during the COVID-19 pandemic and most of them lead a sedentary lifestyle [19].…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study show that significant changes have occurred, including decreased physical activity and increased sedentary, sleep and screen time [18]. Similar to our results are data from a study conducted in Saudi Arabia, according to which most students report poor physical activity during the COVID-19 pandemic and most of them lead a sedentary lifestyle [19].…”
Section: Discussionsupporting
confidence: 87%
“…Differences in self-reported weight, BMI, and percentage body weight were present to a greater extent in subjects with a self-reported worsened lifestyle, and, although emotional feeding behaviour was associated with a greater BMI, most of the association was related to differences in lifestyle during lockdown. Other studies have found that increased sedentary time, disturbed sleep, time spent on social media, and increased working time at home are associated with weight gain during lockdown [ 12 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of university students from Eastern Asia changes in body mass index after lockdown occurred in 54% (32% increased body mass index (BMI) and 22% lost weight) [ 12 ]. Worsening mental health, sleep, dietary, and other lifestyle components markedly occurred in those who experienced weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…For university students, various changes in their academic life occurred, such as restrictions in access to campus and increased online classes. A prospective cohort study conducted before and during the COVID-19 lockdown amongst university students in Saudi Arabia showed that physical activity had decreased, sedentary time had increased, and that although their level of sleeping had decreased but sleeping time had increased (Jalal, Beth, Al-Hassan, & Alshealah, 2021). A cross-sectional survey amongst medical students in nine countries including Japan reported that 90% of respondents mentioned a transition to online education, and 96% of students increased their time spent in front of screens such as computers, cell phones, tablets, and others electronic devices (Perez-Dominguez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%